Pengaruh Religiusitas Dan Pengetahuan Produk Terhadap Keputusan Boikot Konsumsi Produk Milo Di Kabupaten Kerinci Dan Kota Sungai Penuh - Muhammad Wazini; Dafiar Syarif; Muhammad Aunurrochim Bin Mas’ad Saleh; Bustami (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to analyze the influence of religiosity and product knowledge on the decision to boycott the consumption of Milo products in Kerinci Regency and Sungai Banyak City. Using a quantitative approach, data was collected through questionnaires distributed to respondents who are Aqua consumers in these two areas. The analytical tool used namely using Multiple Linear Regression with the help of the IBM SPSS application. Data processing was carried out using regression analysis to test the relationship between the variables religiosity, product knowledge, and the decision to boycott. The results of the research show that religiosity has a significant influence on the decision to boycott consumption of Aqua products, showing that values Religious values can motivate consumers to boycott certain products. Apart from that, product knowledge also has a significant influence on boycott decisions, indicating that the information consumers have about a product can influence their attitudes towards that product. These findings provide important insights for companies and governments in managing the impact of consumer boycotts of certain products. Increasing understanding of religious values and product knowledge can be an effective strategy in reducing the risk of consumer boycott decisions. This research also contributes to the literature on consumer behavior and boycott decisions in local contexts.